Direct and indirect pathway neurons in ventrolateral striatum differentially regulate licking movement and nigral responses - Zhaorong Chen; Zhi-Yu Zhang; Wen Zhang; Taorong Xie; Yaping Li; Xiao-Hong Xu; Haishan Yao (Cell Reports, 2021)
Summary: Drinking behavior in rodents is characterized by stereotyped, rhythmic licking movement, which is regulated by the basal ganglia. It is unclear how direct and indirect pathways control the lick bout and individual spout contact. We find that inactivating D1 and D2 receptor-expressing medium spiny neurons (MSNs) in the ventrolateral striatum (VLS) oppositely alters the number of licks in a bout. D1- and D2-MSNs exhibit different patterns of lick-sequence-related activity and different phases of oscillation time-locked to the lick cycle. On the timescale of a lick cycle, transient inactivation of D1-MSNs during tongue protrusion reduces spout contact probability, whereas transiently inactivating D2-MSNs has no effect. On the timescale of a lick bout, inactivation of D1-MSNs (D2-MSNs) causes rate increase (decrease) in a subset of basal ganglia output neurons that decrease firing during licking. Our results reveal the distinct roles of D1- and D2-MSNs in regulating licking at both coarse and fine timescales.